The Structure and Stability of Molybdenum Ditelluride Thin Films - Zhouling Wang; Wenwu Wang; Ya Yang; Wei Li; Lianghuan Feng; Jingquan Zhang; Lili Wu; Guanggen Zeng (International Journal of Photoenergy)
Molybdenum-tellurium alloy thin films were fabricated by electron beam evaporation and the films were annealed in different conditions in N2 ambient. The hexagonal molybdenum ditelluride thin films with well crystallization annealed at 470°C or higher were obtained by solid state reactions. Thermal stability measurements indicate the formation of MoTe2 took place at about 350°C, and a subtle weight-loss was in the range between 30°C and 500°C. The evolution of the chemistry for Mo-Te thin films was performed to investigate the growth of the MoTe2 thin films free of any secondary phase. And the effect of other postdeposition treatments on the film characteristics was also investigated.